(untitled) (Journal of Hama University, 2026)
The research seeks to study the effectiveness of the rhythm of alliteration in Abu Tammam’s poetry through a semantic study. Therefore, the research begins with an introduction that includes a discussion of the meaning of the term, then it follows up with a study of the contrast in two aspects: the contrast – perfect parallelism, the contrast – incomplete parallelism. The Keywords: Abu Tammam, contrast, rhythm, meaning, coherence.